Genetic differentiation among Atlantic cod (Gadus morhua L.) in Icelandic waters: temporal stability - Jónsdóttir, Ó. D. B.; Daníelsdóttir, A. K.; Nævdal, G. (ICES Journal of Marine Science, 2001)
Temporal variability in genetic structure of Atlantic cod was investigated at two locations (Loftstaðahraun and Kantur) on the main cod spawning grounds off south Iceland using synaptophysin ( Syp I) and haemoglobin as genetic markers. During the spawning season (late March and early April) cod were sampled at each sampling location and then at the same locations two to four weeks later, during two consecutive years (1997 and 1998). Significant genetic differences were found at the Syp I locus between the two samples (Loftstaðahraun and Kantur) and the difference was temporally stable. Very low variation was found in the haemoglobin and no temporal changes were found for this marker. The results strongly indicates that cod in south Icelandic waters do not belong to one panmictic population and that this genetic difference is stable from year-to-year.